Hemophagocytic Syndrome in a Four Year Old Male Child with Plasmodium Vivax Infection - Bhatia, Ravi; Bhatia, Gunjan (Journal of Nepal Paediatric Society, 2016)
In Hyper endemic zones Malaria is known to present with unusual complications. Haemophagocytic syndrome is a disorder of mononuclear phagocytic syndrome. There are many published reports of haemophagocytic syndrome due to P. falciparum infection but haemophagocytic syndrome due to P. vivax infection is quite rare. J Nepal Paediatr Soc 2016;36(2):193-195.